Pengaruh Postnatal Yoga Terhadap Kualitas Tidur Ibu Postnatal Di Wilayah Kerja Puskesmas Kotabumi II Kabupaten Lampung Utara - Aprina Aprina; Rilyani Rilyani; Mela Parosaliantika (Universitas Malahayati Lampung, 2021)
ABSTRACT: THE EFFECT OF POSTNATAL YOGA ON SLEEP QUALITY OF POSTNATAL WOMEN IN THE WORKING AREA OF PUSKESMAS KOTABUMI II, NORTH LAMPUNG DISTRICT Background: Poor sleep in post-natal mothers can cause physiological and psychological balance disorders. Most postpartum women experience sleep disturbance and only 1.9% of women do not wake up during the night during the puerperium and breastfeeding. one of the interventions that can be done is to do postnatal yoga.Objective: The research objective was to determine the effect of postnatal yoga on the quality of sleep of postnatal mothers in the working area of Kotabumi II Public Health Center, North Lampung Regency in 2020.Research Methods: This type of quantitative research and quasy experimental approach. The population in the study were all 48 postpartum mothers with a sample of 28 samples taken by purposive sampling. The object in the study was postnatal yoga, the subject in the study was the quality of sleep for postnatal mothers. The method of collecting data using a questionnaire. The research was conducted in the working area of Puskesmas Kotabumi II, North Lampung Regency in May - June 2020. univariate (average) and bivariate (t test) data analysis.Results: It is known that the mean sleep quality in postnatal mothers before intervention is 8.79 after postnatal yoga is 5.50. There is an effect of postnatal yoga on the quality of sleep for postnatal mothers (P-value 0.000 and t-test t count, 13.663 1.291).Conclusion: There is an effect of postnatal yoga on the quality of sleep of postnatal mothers in the working area of the Kotabumi II Public Health Center in North Lampung Regency in 2020. Pay more attention to their physical and psychological conditions during the postnatal period by keeping themselves from poor sleep quality, by doing yoga exercises regularly in accordance with recommended by health workers Keywords: Post Natal Yoga, Sleep Quality, Childbirth INTISARI: PENGARUH POSTNATAL YOGA TERHADAP KUALITAS TIDUR IBU POSTNATAL DI WILAYAH KERJA PUSKESMAS KOTABUMI II KABUPATEN LAMPUNG UTARA Pendahuluan: Tidur yang tidak berkualitas pada ibu post natal dapat menyebabkan gangguan keseimbangan fisiologis dan psikologis. Sebagian besar wanita nifas mengalami gangguan tidur dan hanya 1,9% saja wanita yang tidak terbangun pada malam hari selama masa nifas dan menyusui. salah satu intervensi yang dapat dilakukan adalah melakukan postnatal yoga.Tujuan: Tujuan penelitian diketahui pengaruh postnatal yoga terhadap kualitas tidur ibu postnatal di wilayah kerja Puskesmas Kotabumi II Kabupaten Lampung Utara tahun 2020.Metode: Jenis penelitian kuantitatif dan pendekatan quasy eksperimen. Populasi dalam penelitian adalah seluruh ibu nifas sebanuak 48 dengan sampel sebanyak 28 pengambilan sampel secara purposive sampling. Objek dalam penelitian adalah postnatal Yoga, subjek dalam penelitian adalah kualitas tidur ibu nifas. Metode pengambilan data dengan menggunakan kuesioner. Penelitian telah dilaksanakan di wilayah kerja Puskesmas Kotabumi II Kabupaten Lampung Utara pada bulan 14 -31 Juli 2020. analisis data secara univariat (rata-rata) dan bivariat (uji t).Hasil: Diketahui diketahui mean kualitas tidur pada ibu nifas sebelum pemberian intervensi 8,79 setelah dilakukan postnatal yoga 5,50. Ada pengaruh postnatal yoga terhadap kualitas tidur ibu postnatal (P-value 0,000 dan uji t t-test t hitung, 13,663 1,291 ) .Kesimpulan: Ada pengaruh postnatal yoga terhadap kualitas tidur ibu postnatal di wilayah kerja Puskesmas Kotabumi II Kabupaten Lampung Utara tahun 2020 Lebih memperhatikan kondisi fisik dan psikisnya selama menjalani masa nifas dengan menjaga dirinya dari kualitas tidur yang buruk, dengan cara melakukan senam yoga secara rutin sesuai dengan yang disarankan oleh petugas kesehatan Kata Kunci : post natal yoga, kualitas tidur, nifas